Consumption Patterns of Food Sources of Iodine and Goitrogenic Substances with the Incidence of Gaky in Coastal Areas - Sudirman Sudirman; Rezqiqah Aulia Rahmat; Djunaedi Djunaedi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Iodine Deficiency Disorders (IDD) are a public nutritional problem still found in several regions, including coastal areas. This condition is influenced by inadequate iodine intake and the consumption of foods containing goitrogenic substances that can inhibit iodine absorption. This study aims to determine the relationship between consumption patterns of foods containing iodine and goitrogenic substances and the incidence of IDD in coastal areas. This study used quantitative methods with an analytical design and a case-by-case approach. control. The sample consisted of a case group (people with IDD) and a control group (people without IDD). Data were collected through a food consumption frequency questionnaire and analyzed using the Chi- Square test. The results showed that low consumption of iodine-rich foods and high consumption of goitrogenic foods were significantly associated with the incidence of IDD (p < 0.05).